ANALISA PENGARUH GAYA KEPEMIMPINAN, BUDAYA LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP LOYALITAS KINERJA KARYAWAN PADA PT MULTI ASIA SATU - Oktaviani, Nurullita; Purnawan, Yohan; siagian, Riduan (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2023)
Abstract: This research aims to find out if there is a significant influence of leadership styles, culture, work environment and the motivation of loyalty against the performance of employees at PT Multi Asia Satu. A sample of these studies amounted to 33 employees working PT. Multi Asia Satu. Sampling techniques using sampling of saturated. This research uses the time horizon that is cross sectional. The research methodology used is a quantitative research methodology, with the kind of descriptive research and associative. Data collection is done using questionnaire and the study of the literature. The results showed that there was no significant influence between the leadership style and the culture of the work environment against employee performance and loyalty, there was significant influence between the motivation of loyalty against the performance of employees. The results of this study suggest the company is expected to give awards for employees who perform so that employees are motivated in their work.